Penguatan Pemahaman Masyarakat Kelurahan Penggaron Lor Kecamatan Genuk Kota Semarang Mengenai Pembagian Waris Islam - Abib, Agus Saiful; Triwati, Ani; Sihotang, Amri Panahatan (Fakultas Hukum Universitas Semarang, 2024)
The distribution of Islamic inheritance is currently regulated by Article 171-191 of Presidential Instruction Number 1 of 1991 concerning the Compilation of Islamic Law with the consideration that it is in order to resolve problems that exist in society regarding marriage, inheritance and waqf. These disputes and quarrels often result in the breaking of ties of friendship between them, sometimes even resulting in physical attacks or even murder due to disputes over inheritance. Based on data, inheritance disputes rank second in religious courts after divorce cases. So far, many people do not know about the distribution of Islamic inheritance, therefore it is necessary to provide community service in the form of strengthening the understanding of the Penggaron Lor Genuk Semarang community regarding the distribution of Islamic inheritance. This service is carried out by means of lectures and direct question and answer and evaluation by distributing questionnaires before and after the activity is carried out. This service is carried out by an implementing team consisting of 1 (one) chairman and 2 (two) members. The implementing team is lecturers from the Faculty of Law, University of Semarang who are competent in mastering material regarding the distribution of Islamic inheritance. The results of the service which took the theme of the rights of people with disabilities have increased by an average of 67.3%.